A Conceptualization of remote Auditing framework - Dlamini, Zenani (College of Accounting, 2024)
Auditing was an activity that was typically performed from the audit client's premises or the auditor's offices. If the audit client had significant components in other countries, the lead auditor would appoint a component auditor within that country to perform the audit work to support the group engagement team's audit opinion. Globalization and the COVID-19 pandemic changed the audit environment leading to the environment becoming more digitized. The pandemic enforced a work-from-home strategy; thus, audit fieldwork had to be performed remotely. Studies around the remote auditing model suggested that it would lead to lower audit quality and professional skepticism due to the lack of physical presence. Furthermore, previous research on the remote auditing model was performed from the perspective of component auditors, internal auditors, or information technology (IT) auditors. This study aimed to explain the structure and positioning of the remote audit environment in the traditional audit framework. To date, no academic study has explored the structure of the remote audit environment and its position in the context of the traditional audit framework. Using the SCP paradigm and the Unified Services Theory, this study filled an important research gap in the auditing literature. It was used as a base to understand the remote audit environment. This qualitative study collected data using semi-structured interviews to answer the research questions. The findings from this study found that the remote auditing model was a preexisting model which could have been implemented before the COVID-19 pandemic; however, there was no demand for it. The pandemic's impact and technological changes exacerbated the need for a remote audit environment. The results also indicated that remote audit firms operated as a support structure to traditional audit firms. However, they offered a level of competition from a South African perspective. Furthermore, in assessing the audit quality measures in the remote audit environment, it was noted that they were no different from those of traditional audit firms. Finally, the results indicated the presence of some limitations to the remote audit environment. Keywords: remote audit, audit quality, technology, consequence management, global business services, COVID-19